The Differences of the Student Learning Outcome Using Realistic Mathematics Learning Approaches (PMR) And Contextual Learning Approaches (CTL) on the Sets Material - Rahmawati, Nurina Kurniasari; Amah, Amah (Al-Jabar: Jurnal Pendidikan Matematika, 2018)
This research aims to determine differences in learning outcomes of students who use Realistic Mathematics Learning (PMR) and Contextual Approach (CTL) approaches on the set Material. This research method is quasi experiment with posttest only control design. The sampling technique was used cluster random sampling with 2 experimental classes These are experimental class 1 (the class was treated with the Realistic Mathematics Education (PMR) approach and experimental class 2 (the class was treated with the Contextual Learning (CTL) approach The hypothesis test is used the t-test. The results of the research is found that there were differences between the student learning outcome in the set material using Realistic Mathematics Learning (PMR) approach and the student learning outcome in the set material using the Contextual Learning approach (CTL). Because the student learning outcome in the set material using Realistic Mathematics Learning (PMR) approach better than the student learning outcome in the set material using the Contextual Learning approach (CTL).